ՀՀ Երիտասարդների աշխատանքային գաղթ․ փորձագիտական ընկերաբանական ուսումնասիրութիւն - Շահինեան, Անդրանիկ (տպ. Atlas)
This article reviews a sociological examination based on qualitative research and analysis on the issue of youth labor migration. The issue under consideration was considered during a study of a sample of young people with a migration trend and related it to gender, age and social status, as part of a scientific study conducted in the Republic of Armenia. Among the experts are specialists of public and state-branch structures. As part of the research of the article, we examined the concepts of "migration" and "development", in particular, in connection with the process of youth development, and emphasized the importance of youth employment issues, which are the cause of foreign labor migration of young people from the RA. In the framework of the research, we also addressed the negative consequences of labor migration and risks in the process of self-realization of young people as well as issues of choosing a profession and choosing destination countries. We also considered the issues of safe movement, taking into account the advice of experts regarding the structures dealing with this problem.
Keywords: Աշխատանքային գաղթ; Միգրացիա